Crassocephalum crepidioides extracts reverses the effects of valproic acid in an in-utero mouse model of autistic disorders - Folefack, Irene Alice; Djiogue, Sefirin; Beppe, Jean G.; Allah-Doum, Nanou Gael; Adjoffoin, Chiara N.; Djikem, Rudig Nikanor T.; Barga, Bertrand M.; Atsama, Perpetue M.; Sadou, Woudamkine; Ngo Bum, Elisabeth (International Journal of Research in Medical Sciences, 2025)
Background: Autism spectrum disorder (ASD) is a heterogeneous neurodevelopmental condition characterized by deficits in social communication and interaction, alongside restricted or repetitive behaviours. This study investigates the potential of hydroethanolic extract of Crassocephalum crepidioides (HEE) to ameliorate ASD-related behaviours in a valproic acid (VPA)-induced mouse model of in utero ASD. VPA exposure disrupts neurodevelopmental processes, affecting synaptic function and neural connectivity which are also seen in Autism. Methods: Thirty pregnant female mice were used among which, six served as normal control group. the twenty-four remaining mice received valproic acid 600 mg/kg on gestational day 10 to day 12. Following parturition, offspring were treated daily from postnatal day 21 to 50. Behavioural assessments were conducted during the treatment period. Upon completion of behavioural testing, brains were collected for biochemical analysis of monoamine levels. Results: Compared to the VPA-exposed control group, HEE treatment at all tested doses significantly reduced (p<0.001) the time spent investigating an empty chamber in a social preference test, and significantly increased (p<0.001) the time spent interacting with a social stimulus (sentinel). Furthermore, HEE treatment significantly increased (p<0.001) brain tissue concentrations of monoamines. Conclusions: These findings suggest that Crassocephalum crepidioides extract may exert neuroprotective effects, improving both social behaviour and reducing repetitive behaviours in this VPA-induced mouse model of ASD. HEE has therapeutic potential by modulating neurotransmitter systems known to be disrupted in Autism.